DZIKIR: - Dimyati Sajari (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
There is different motivation in performing dhikr between the lay people and the Sufis. When people in general (the laity) have felt getting peace of mind only with dhikr, but the Sufis have not gotten sobriety essential simply with this dhikr. The Sufis found that dhikr without the feeling of unity with God could not provide tranquility and sobriety. Sufis obtain real sobriety when they felt close to God, even united with Him (taqarrub ilâ Allâh). This paper describes the purpose and significance of dhikr among the Sufis. Hence, the information can be of importance for lay people to increase their motivation of dhikr to Allah The Almighty.